Streamlining Warehouse Process: A UHF RFID-Enabled Smart Warehouse System Design - Soesanto, Rayinda Pramuditya; Nurdiansyah, Yodi; Kurniawati, Amelia (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
In the era of digital transformation, the Internet of Things (IoT) has emerged as a pivotal force in information technology. This research addresses the pressing need for companies to integrate IoT technology, specifically Ultra-High Frequency Radio-Frequency Identification (UHF RFID), into their warehouse systems. The study aims to tackle the challenges faced by companies during peak periods, such as online shopping promotions, where transaction volumes surge, demanding efficient inventory and shipment management. The proposed solution involves implementing an IoT-based warehouse management system leveraging UHF RFID technology. This system seeks to optimize inventory and shipment management through real-time data collection, processing, and analysis. By continuously monitoring inventory and delivery processes, companies can swiftly identify and address issues. The integration of UHF RFID with the information system not only enhances order fulfillment efficiency during peak times but also reduces costs and time associated with inventory management. This research advocates for the strategic adoption of an IoT-based warehouse management system, emphasizing the benefits of UHF RFID integration, including enhanced accuracy, reduced labor costs, and overall improved business efficiency. The findings provide valuable insights into the practical implementation of IoT technologies, offering a roadmap for companies seeking to optimize warehouse operations and meet customer demands with precision in today's competitive digital landscape.